Static Characterization of the Birefringence Effect in the Semiconductor Optical Amplifier Using the Finite Difference Method - A. Elyamani; A. Zatni; H. Bousseta; A. Moumen (Institute of Advanced Engineering and Science, 2015)
Knowing the various physical mechanisms of the semiconductor optical amplifier (SOA) helps us to develop a more complete numerical model. It also enables us to simulate more realistically the static behavior of the SOAs’ birefringence effect. This way, it allows us to study more precisely the behavior of SOAs, and particularly the impact of the amplified spontaneous emission (ASE) or the pump and probe signals as well as the optical functions based on the non-linearity of the component. In static regime, the SOAs possess a very low amplification threshold and a saturation power of the gain which mainly depends on the optical power injected into the active region. Beyond the optical input power, the SOA is in the saturated gain regime which gives it a nonlinear transmission behavior. Our detailed numerical model offers a set of equations and an algorithm that predict their behavior. The equations form a theoretical base from which we have coded our model in several files.cpp that the Language C++ executes. It has enabled us, from the physical and geometrical parameters of the component, to recover all the relevant values ​​for a comprehensive study of SOAs in static and dynamic regimes. In this paper, we propose to make a static characterization of the effect of the nonlinear polarization rotation by realizing a pump-probe assemblage to control the power and state of polarization at the entering of the SOA.